Crecimiento de Macrobrachium rosenbergii (Crustacea- Palaemonidae) cultivado en estanques, sin alimentación suplementaria (ING) - Cabrera Peña, Jorge (1995)
From October 1984 to February 1985, a study was carried out in order to determine the growth of Macrobrachium rosenbergii culture in seminatural ponds. The mean caparace length increase for this specie was 23,5 ± 6,75 mm/month. The relationships caparace length-time and caparace length-weight were Lc = 0.312+0.7332 t and P= 9.68 x 10-5 Lc2.985 respectively. The total mortality was 37.4%.